'Thank you in advance' - Orthaber, Sara (Scripta manent (Ljubljana), 2017)
Communication through email represents one of the most important forms of business communication, not just within a company but also externally with customers. The paper examines email interactions between the agents representing a Slovenian transport company and its customers. More specifically, the study examines specific aspects and elements of email production in a Slovenian customer service setting. It is hoped that the findings will help enhance the communication skills of learners of Slovenian as a foreign language and students of translation and increase their cultural awareness and their knowledge of technology-mediated customer service communication. Moreover, the findings could increase students' understanding of the pragmatic motivations behind interactants' linguistic choices.
Keywords: Analiza vsebine; e-komunikacija; elektronska sporočila; Elektronsko poslovanje; email communication; e-mails; institutional interaction; ne zaključna dela; poslovna komunikacija; Poslovno komuniciranje; Slovene language; slovenščina